Enemy in the Mirror: Islamic Fundamentalism and the Limits of Modern Rationalism: A Work of Comparative Political Theory by Roxanne L. Euben (Princeton, New Jersey: Princeton University Press; 1999. 239 pages.) (American Journal of Islam and Society, 2002)
In recent months, the media has been saturated with endless discussions on Islamic fundamentalism. People with little or no training in Islamic studies have been paraded in front of viewers and readers presenting useless, and at times mindless, commentary on Islamic theology and fundamentalism.Amid all this hyperbolic discussion, a refreshing and cogent analysis can be found in Roxanne L. Euben's excellent Enemy in the Mirror: Islamic Fundamentalism and the Limits of Modern Rationa lism. Euben, a Princeton Ph.D. who teaches political science at Wellesley College, offers a forceful illumination of Islamic fundamentalism, particularly the thought of Sayyid Qutb.In this serious and intelligent work of comparative politics and political theory, Euben seeks, through an interpretive approach, to understand the fundamentalists' own understanding of their meaning and purpose. She argues that Qutb's political thought is an indictment not only of western imperialism and colonialism, corrupt Middle Eastern governments, or modernity per se, "but also of modem forms of sovereignty and the western rationalist epistemology that justifies them." Euben maintains that Qutb's thought is neither unique nor idiosyncratic when compared to other Islamic fundamentalists. Yet she does not stop there - she argues that Qutb's critique of the modern condition shares many similarities with Christian fundamentalists as well, and even with neoliberal political philosophers. By situating Qutb in a crosscultural comparative context, Euben undermines the perceived opposition between "us" and "them" or "Islam" and "the West." Instead, she maintains that Qutb and others should be viewed as part of an international thrust preoccupied with the "erosion of values, traditions, and meanings" that is seen as constitutive of post-Enlightenment modernity. Thus, Euben invites the reader to view Qutb and his theories through a critical analytical prism that is both instructive and enlightening. Euben's book is divided into six chapters. The first two frame the general questions, define the key terms, and construct the book's methodology. It is clear that Euben is seeking to make sense, via a dense theoretical discourse, of the rise of religious fundamentalism or what she calls "foundationalist political practice." This task is problematic, she argues, given that political science no longer sees any place for metaphysics in political life. This makes it difficult to interpret practices and actions guided by belief in divine truth. Furthermore, the discipline is grounded in a this-worldly scholarly discourse that finds "foundationalist political practice" a threat to modern politics and hence a menace to modem society (e.g., Samuel Huntington) ...